Multiple, Coeval Silicic Magma Storage Domains Beneath the Laguna Del Maule Volcanic Field Inferred From Gravity Investigations. Issue 4 (1st April 2021) - Trevino, Sarah F.; Miller, Craig A.; Tikoff, Basil; Fournier, Dominique; Singer, Brad S.
Abstract: The rhyolite‐producing Laguna del Maule volcanic field (LdMVF), Chile, has had numerous post‐glacial eruptions that produced large explosions and voluminous lava flows. During the Holocene ∼60 m of surface uplift is recorded by paleo‐shorelines of the fresh‐water Laguna del Maule, with an inflation source near the Barrancas volcanic complex. Rhyolites from the Barrancas complex erupted over ∼14 ka including some of the youngest (1.4 ± 0.6 ka) lava flows in the field. New gravity data collected on the Barrancas complex reveals a residual gravity low (−6 mGal, "Barrancas anomaly") that is distinct from the pronounced gravity low (−19 mGal; "Lake anomaly") associated with present‐day ground uplift to the northwest. Three‐dimensional inversion of the Barrancas anomaly indicates the presence of a magma body with a maximum density contrast with the host rock of −250 kg/m 3 centered at a depth of ∼3 km below surface. Nearby Miocene high‐silica granites represent frozen remnants of highly evolved rhyolitic magma. Comparison of the densities measured from samples of these plutons with the geophysical model densities, and integration of thermodynamic modeling of silicic melt evolution, provide constraints on our interpretation. We propose a magma body, containing <30% melt phase and low volatile content, exists beneath Barrancas. The Barrancas and Lake gravity lows represent magma in different physical states, associated with past and present‐day storage beneath LdMVF. The gravity model mirrors geochemical observations which independently indicate that at least two distinct rhyolites were generated and stored as discrete magma bodies within the broader LdMVF. Plain Language Summary: The Laguna del Maule volcanic field (LdMVF) in Chile, has a long history of eruptions that produced large explosions and voluminous lava flows. Lava emitted during these eruptions comes from shallow sources of partially molten rock (magma) located a few kilometers below the surface. Magma pushing from below and into these shallow regions has caused the ground around the lake to rise over the last 10, 000 years. To understand the causes of deformation and assess the likelihood of future eruptions, it is essential to know the location and present‐day state of magma within Earth's crust. Magma is typically less dense than the surrounding rock and these density variations cause small changes in the local gravity field, detectable with geophysical instruments. We collected a new set of gravity measurements at the Barrancas volcanic complex to determine if magma is present beneath the volcano that last erupted about 2000 years ago. Our data reveal a shallow magma body at depth beneath the Barrancas complex. This new magma body is separate from another magma body located in a different part of the LdMVF, which has important implications for the assessment of future volcanic hazards in the region. Key Points: At least two separate magma storage regions in different physical states exist beneath the Laguna del Maule volcanic field A −6 mGal gravity anomaly below the Barrancas complex is close to a postulated inflation source which produced ∼62 m of Holocene uplift Comparing model densities to nearby plutons and seismic models indicates Barrancas magma is above solidus with a small melt proportion